The evolution of antibody-secreting cell biological exploration: one mouse model at a time - Pioli, KimAnh Trang; Pioli, Peter Dion (Frontiers in Immunology, 2026)
Upon antigenic exposure, B cells become activated and undergo differentiation into antibody-secreting cells (ASCs) which secrete thousands of antibodies per second. However, ASCs have shown themselves to be a heterogenous population which possesses capabilities well beyond just antibody secretion. Therefore, a growing need exists to more comprehensively assess ASC biology. As the rise of genetically modified mouse models has allowed for substantial gains in our understanding of immune system development and function, it also enables the exploration of ASC development and function. This Perspective article aims to highlight the evolution in mouse models which have facilitated the advancement of ASC research in areas including development, function, heterogeneity and longevity. Furthermore, we discuss the future of ASC mouse models as it pertains to their potential of furthering our understanding of ASC biology in health and disease.